2016
DOI: 10.1063/1.4941560
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of covalency, hydrogen bonding, and dispersion leads to a long range chiral network: The example of 2-butanol

Abstract: The assembly of complex structures in nature is driven by an interplay between several intermolecular interactions, from strong covalent bonds to weaker dispersion forces. Understanding and ultimately controlling the self-assembly of materials requires extensive study of how these forces drive local nanoscale interactions and how larger structures evolve. Surface-based self-assembly is particularly amenable to modeling and measuring these interactions in well-defined systems. This study focuses on 2-butanol, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…The DFT calculated structure for the hydrogen bonded tetramer shows that each 2-BuOH molecule again binds to preferred Au atop sites, with the OH group almost parallel to the surface while the hydrocarbon tail tilts away from the surface. 20 Similar to the achiral C 1 -C 3 alcohols investigated before, point chirality develops when the chiral 2-BuOH molecule adsorbs on the Au atom via the oxygen lone pair. As such, the 2-BuOH molecules can have both intrinsic and surface-bound chiral centers.…”
Section: E (R)-and (S)-2-buoh On Au(111)mentioning
confidence: 83%
See 2 more Smart Citations
“…The DFT calculated structure for the hydrogen bonded tetramer shows that each 2-BuOH molecule again binds to preferred Au atop sites, with the OH group almost parallel to the surface while the hydrocarbon tail tilts away from the surface. 20 Similar to the achiral C 1 -C 3 alcohols investigated before, point chirality develops when the chiral 2-BuOH molecule adsorbs on the Au atom via the oxygen lone pair. As such, the 2-BuOH molecules can have both intrinsic and surface-bound chiral centers.…”
Section: E (R)-and (S)-2-buoh On Au(111)mentioning
confidence: 83%
“…Contrary to the 3-fold symmetry of the Au(111) surface, it was found that the formation of tetramers was more energetically preferred than dimers and trimers. 20 DFT calculations also found that hydrogen bonded tetramers were equally as stable as hydrogen bonded hexamers but hexameric units were not observed in the surface coverages explored. The DFT calculated structure for the hydrogen bonded tetramer shows that each 2-BuOH molecule again binds to preferred Au atop sites, with the OH group almost parallel to the surface while the hydrocarbon tail tilts away from the surface.…”
Section: E (R)-and (S)-2-buoh On Au(111)mentioning
confidence: 89%
See 1 more Smart Citation
“…Obviously, Δ E int depends on all the interactions, therefore in this case the disentanglement of XB results to be particularly interesting. Moreover, Δ E int takes into account also the electrostatic interaction between the fragments, which always plays an important role in HBs and XBs . Interestingly, the trend of the dissociation energies is slightly different: −20.3, −18.3, and −11.6 kcal/mol for NIS, NBS, and NCS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As regards the liquid-vapor interface, we also note a slight orientation of alcohol molecules parallel to the interface to a lesser degree than water. Let us recall that even in bulk conditions, alcohol molecules form chainlike structures [85][86][87][88] which are less cohesive than the 3D-HB network of water.…”
Section: Please Cite This Articlementioning
confidence: 99%